Cytotoxic triterpenoids from the roots of Bupleurum scorzonerifolium. (February 2023) - Li, Dan-Qi; Zhao, Zi-Wei; Jiang, Fan; Liu, Da; Wu, Xiao-Jing; Liu, Xue-Gui; Gao, Pin-Yi
Abstract: As a part of our ongoing studies on cytotoxic triterpenoids from the genus Bupleurum, a 70 % ethanol extract of Bupleurum scorzonerifolium Willd. was systematically separated by silica gel column chromatography, HP-20 macroporous resin column chromatography, ODS column chromatography and HPLC, 15 triterpenoids were obtained, of which two were new compounds. Their structures were elucidated by 1D and 2 D NMR, HR-ESI-MS, and other spectroscopic methods. Additionally, these compounds were evaluated for their cytotoxic activities against four selected cancer cell lines using the MTT assay. Some of the isolated compounds exhibited appreciable cytotoxic activities against these four human cancer cell lines. Graphical Abstract: ga1 Highlights: 15 triterpenoids saponins were isolated from the roots of Bupleurum scorzonerifolium Willd. (Apiaceae). Two new compounds were elucidated by spectroscopic methods. The cytotoxicity of all isolates were assessed against four cancer cell lines via the MTT assay. Five saponins (1, 6, 8, 11 and 12 ) exhibited significant cytotoxicity.